Computing plasma focus pinch current from total current measurement - Lee, S.; Saw, S. H.; Lee, P. C. K.; Rawat, R. S.; Schmidt, H. (AIP Publishing, 2008)
The total current Itotal waveform in a plasma focus discharge is the most commonly measured quantity, contrasting with the difficult measurement of Ipinch. However, yield laws should be scaled to focus pinch current Ipinch rather than the peak Itotal. This paper describes how Ipinch may be computed from the Itotal trace by fitting a computed current trace to the measured current trace using the Lee model. The method is applied to an experiment in which both the Itotal trace and the plasma sheath current trace were measured. The result shows good agreement between the values of computed and measured Ipinch.